DEVELOPING ORGANIZATIONAL ASPECTS OF POLDER INSTITUTION CASE STUDY: BANGER RIVER, SEMARANG - Nanang Rianto (Widyariset, 2012)
This qualitative research about composing the organizational aspect of polder board used case study method.Findings show that the suitable organizational form for Banger Polder System is a board that: 1) reflects theside who give direction; 2) reflects the responsibility to both internally (community) and externally (City Major);3) involve the internal and external stakeholders for operational and maintenance tasks; 4) the capacity andcomposition of the member organization (board direction) reflects the stakeholders support and interest related tooperational and maintenance tasks.